Genetic Diversity of Freshwater Leeches in Lake Gusinoe (Eastern Siberia, Russia) - Irina A. Kaygorodova; Nadezhda Mandzyak; Ekaterina Petryaeva; Nikolay M. Pronin (The Scientific World Journal)
The study of leeches from Lake Gusinoe and its adjacent area offered us the possibility to determine species diversity. As a result, an updated species list of the Gusinoe Hirudinea fauna (Annelida, Clitellata) has been compiled. There are two orders and three families of leeches in the Gusinoe area: order Rhynchobdellida (families Glossiphoniidae and Piscicolidae) and order Arhynchobdellida (family Erpobdellidae). In total, 6 leech species belonging to 6 genera have been identified. Of these, 3 taxa belonging to the family Glossiphoniidae (Alboglossiphonia heteroclita f. papillosa, Hemiclepsis marginata, and Helobdella stagnalis) and representatives of 3 unidentified species (Glossiphonia sp., Piscicola sp., and Erpobdella sp.) have been recorded. The checklist gives a contemporary overview of the species composition of leeches and information on their hosts or substrates. The validity of morphological identification of each taxon has been verified by phylogenetic approach with a molecular marker adopted for a DNA barcoding of most invertebrates.